Component variability of phraseological units and transformation mechanisms in literary translation - Sadikova , Saodat Minovarovna (The Lingua Spectrum, 2026)
This study explores the variability of components and the mechanisms of transformation of phraseological units in literary translation. It argues that the translator’s task extends far beyond the mere transfer of semantic content, requiring the recreation of the stylistic, emotional, expressive, and aesthetic impact embedded in the source text. Phraseological units serve as important carriers of figurative meaning, cultural connotations, and authorial individuality; therefore, their successful translation depends not on literal equivalence, but on the preservation of their semantic nucleus and pragmatic function. The paper defines component variability as the substitution, expansion, reduction, rearrangement, or modification of phraseological elements in ways that maintain the communicative value and artistic effect of the original. Drawing on the theoretical perspectives of V. Vinogradov, E. Nida, and other scholars in translation studies, the research emphasizes the importance of dynamic and functional equivalence over formal correspondence. Particular attention is paid to the influence of linguistic, cultural, and stylistic asymmetries between source and target languages in determining translation strategies.